Antibacterial and antibiofilm activity of peptide PvGBP2 against pathogenic bacteria that contaminate Auricularia auricular culture bags - Shen Yang; Zijin Yuan; Jude Juventus Aweya; Shanggui Deng; Wuyin Weng; Yueling Zhang; Guangming Liu (Food Science and Human Wellness)
Bacteria contamination in Auricularia auricular culture bags reduces yield and increases the risk of food safety. In this study, 5 species of bacteria, mainly gram-positive bacteria including three species of Bacillus spp., Arthrobacter arilaitensis and Staphylococcus warneri, were isolated and identified from bacteria-contaminated A. auricular culture bags. An in silico predicted antimicrobial peptide from the β-1,3-glucan-binding protein sequence of Penaeus vannamei, designated PvGBP2 (FLKLGRKSRYGMLKL), was screened and its antibacterial effect and mechanism of action on the isolated Bacillus spp. explored. The minimal inhibitory concentrations (MIC) of PvGBP2 on Bacillus spp. were 15.6–31.25 μg/mL. Peptide PvGBP2 could inhibit Bacillus subtilis in A. auricular culture bags to maintain growth and yield of A. auricular. Transmission electron microscopy (TEM) revealed that PvGBP2 kills bacteria by perforating the cell wall, destroying membrane integrity and resulting in the leakage of intracellular solutes. In addition, PvGBP2 inhibits biofilm formation by B. subtilis by 90.6 % at 1 × MIC. Thus, peptide PvGBP2 could be potentially applied as an antibacterial agent to control bacterial infection of A. auricular cultivation and the spread of foodborne pathogens.